The HSP90 inhibitor 17-AAG potentiates the antileishmanial activity of the ether lipid edelfosine (2014)
ABSTRACT: HSP90 is an abundant protein in Leishmania parasites that plays a major role in the parasite survival under stress conditions. Here we found that the HSP90 inhibitor 17- AAG (≥100 nM 17-AAG) induced cell cycle arrest at G0/G1 in L. infantum and L. panamensis promastigotes, and highly potentiated the induction of cell death by an apoptotic-like process mediated by the ether phospholipid edelfosine (5-20 μM). These data suggest that the combined treatment of 17-AAG and edelfosine might be a novel and effective approach of combination therapy in the treatment of leishmaniasis.